2021
DOI: 10.1016/j.nicl.2021.102885
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural alterations of the corticospinal tract are associated with poor motor function in patients with severe congenital heart disease

Abstract: Highlights Congenital heart disease (CHD) patients are at risk for developmental impairments. CHD patients have a higher rate of motor impairments compared to controls. Fractional anisotropy of the corticospinal tract (FA CST) is lower in CHD patients. Lower FA CST is associated with poorer motor function in patients with complex CHD. Altered primary motor pathway development may lead to motor impairments in CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…In our study of white matter connectivity using recent diffusion imaging analysis methods in early school-age children with CHD, we show: (1) CHD patients had extensive decreases in white matter connectivity compared to TPC, (2) there were several distinct positive associations between QA and neuropsychological measures within www.nature.com/scientificreports/ CHD patients, and (3) CHD patients had a similar, but less extensive and bilateral hub distribution, than TPC. These results are consistent with previous studies indicating widespread decreased FA in adults and adolescents with CHD and decreases in FA related to worse performance on neuropsychological tests 27 . The current study expands these findings by: (1) investigating a unique, novel cohort of developing children with CHD (survivors of single ventricle palliation) that has not been studied previously using higher-order diffusion analyses; (2) observing white matter connectivity correlations with a comprehensive neuropsychological battery; and (3) performing a hub analysis to reveal differences in network topology in the CHD cohort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study of white matter connectivity using recent diffusion imaging analysis methods in early school-age children with CHD, we show: (1) CHD patients had extensive decreases in white matter connectivity compared to TPC, (2) there were several distinct positive associations between QA and neuropsychological measures within www.nature.com/scientificreports/ CHD patients, and (3) CHD patients had a similar, but less extensive and bilateral hub distribution, than TPC. These results are consistent with previous studies indicating widespread decreased FA in adults and adolescents with CHD and decreases in FA related to worse performance on neuropsychological tests 27 . The current study expands these findings by: (1) investigating a unique, novel cohort of developing children with CHD (survivors of single ventricle palliation) that has not been studied previously using higher-order diffusion analyses; (2) observing white matter connectivity correlations with a comprehensive neuropsychological battery; and (3) performing a hub analysis to reveal differences in network topology in the CHD cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Children with CHD requiring open heart surgery are 15 times more likely to have a brain abnormality than term comparisons 25 . These abnormalities are associated with impairments in IQ, attention, and motor skills 8,[25][26][27] .…”
mentioning
confidence: 99%
“…7 A few studies have reported lower gross motor than fine motor scores. 3,4,[8][9][10][11][12] Reporting motor standard scores or composite scores without the individual subtest scaled scores masks differences between fine and gross motor scores and thus may decrease the recognition of individual deficits and reduce recommended clinical neurodevelopmental interventions. 8,[11][12][13][14][15] Recognising that long-term motor delays may be improved by early interventions, there is a need to study gross motor and fine motor scores separately to aid clinicians in the care of this population.…”
mentioning
confidence: 99%
“…3,4,[8][9][10][11][12] Reporting motor standard scores or composite scores without the individual subtest scaled scores masks differences between fine and gross motor scores and thus may decrease the recognition of individual deficits and reduce recommended clinical neurodevelopmental interventions. 8,[11][12][13][14][15] Recognising that long-term motor delays may be improved by early interventions, there is a need to study gross motor and fine motor scores separately to aid clinicians in the care of this population. [4][5][6]14 Reported acute care predictors of adverse motor outcomes have included a variety of different cardiac defects, especially for those after palliative surgery, imaging determined brain injury, need for anticoagulant medication, longer duration of mechanical ventilation, and longer hospital and intensive care stay.…”
mentioning
confidence: 99%
See 1 more Smart Citation